Survei Penerapan Metode Pembelajaran Daring pada Mata Pelajaran PJOK di SMK Negeri 01 Pabelan Kabupaten Semarang Tahun Pelajaran 2020/2021 - Fauzi, Ridho Imam; Qoriah, Anirotul (Universitas Negeri Semarang, 2023)
This study aims to determine the application of online learning to PJOK subjects during a pandemic. The type of research used is qualitative research. The focus and locus in this study were two teachers and students of PJOK subjects at the State Vocational High School 01 Pabelan. Data collection is carried out using observation, interviews, and documentation. Data analysis is carried out descriptively by explaining, managing, describing, and interpreting the results of the study with the sentence structure of the problem under study. PJOK online learning at The State Vocational High School 01 Pabelan using WhatsApp, Google Meet, and Google Classroom applications to carry out learning cannot run smoothly. There are many obstacles and obstacles when online learning in PJOK subjects that make it difficult for students to understand the material provided by PJOK Teachers. From the results of the study, it was concluded that online learning in PJOK subjects at the State Vocational High School 01 Pabelan, using the WhatsApp application, Google Classroom, and Google Meet as learning media ran less optimally. There are still many obstacles that prevent students from having difficulty understanding the PJOK learning material.